Balancing cohesin eviction and retention prevents aberrant chromosomal interactions, Polycomb-mediated repression, and X-inactivation - Kriz, Andrea J. (Mol Cell, 2021)
Depletion of architectural factors globally alters chromatin structure, but only modestly affects gene expression. We revisit the structure-function relationship using the inactive X chromosome (Xi) as a model. We investigate cohesin imbalances by forcing its depletion or retention using degron-tagged RAD21 (cohesin subunit) or WAPL (cohesin release factor). Cohesin loss disrupts Xi superstructure, unveiling superloops between escapee genes, with minimal effect on gene repression. By contrast, forced cohesin retention markedly affects Xi superstructure, compromises spreading of Xist RNA-Polycomb complexes, and attenuates Xi silencing. Effects are greatest at distal chromosomal ends, where looping contacts with the Xist locus are weakened. Surprisingly, cohesin loss creates an “Xi superloop” and cohesin retention creates “Xi megadomains” on the active X. Across the genome, a proper cohesin balance protects against aberrant inter-chromosomal interactions and tempers Polycomb-mediated repression. We conclude that a balance of cohesin eviction and retention regulates X-inactivation and inter-chromosomal interactions across the genome.